The chinese football development plan: soft power and national identity - Leite Júnior, Emanuel Ferreira (2018)
In April 2016, the People's Republic of China (PRC) launched the "football development plan in the medium and long term (2016-2050)." The Chinese Government's goal is clear: making the Asian country a worldwide football superpower. This article will show how the Chinese strategy is organized in its three stages, with commitments and goals to be reached at the end of each one of them. Including the President Xi Jinping "three World Cup dreams" audacious plans: to qualify for another FIFA World Cup edition, host a World Cup edition and, finally, win a World Cup by 2050 to thus consolidate the country's football power in the most popular sport on the planet. The article also intents to demonstrates how the Chinese state induces private investment in football and sports industry. Showing that the large Chinese conglomerates have beeing collaborated in a crucial manner so that the government achieves the objectives outlined in its plan. And while China is moving towards the development of the most popular sport on the planet, the article brings to the theoretical discussion issues such as soft power and sport's influence, especially football, in the identity and national pride. Brought to a conclusion that the Chinese state has taken advantage of the football popularity to exercise 'soft power', strengthening diplomatic ties and placing the country in the Asian and worldwide context, but also to reinforce their people sense of national identity. For this, the article resorts to the bibliographic review, comparative study, in addition to analyzing the football development plan.